Gender Symbolism in Sampur and Samparan of Surakarta-Style Javanese Dance Costume Design - Sriyadi, Sriyadi; Hartanto, Hartanto; Syahrial, Syahrial; Hapsari, Indri (Universitas Negeri Medan, 2025)
Sampur and samparan are essential elements in the costume design of Surakarta-style female dance, serving as primary visual markers that distinguish the aesthetic characteristics of this dance style. Their presence extends beyond mere costume design in court dances such as bedhaya and srimpi; they also function as properties that must be animated by the dancer to harmonize with the movement patterns employed. This study aims to describe the form, meaning, and characteristics of sampur and samparan in the costume design of Surakarta-style female dance and to analyze their significance in the cultural expression of Javanese society. The research employs an ethnocoreological approach with qualitative methods. Primary data were obtained through participatory observation, in which the researcher was directly involved as a Javanese dancer. The findings reveal that sampur and samparan not only enhance the expressive quality of dance movements through distinctive accentuations but also reflect the cultural values and identity of Javanese society. Specifically, samparan is exclusively used in female dances due to its association with the ideal concept of womanhood in Javanese culture. Thus, sampur and samparan function not only in the visual and technical aspects of performance but also as symbolic elements that reinforce the identity of Javanese dance as an art form rich in philosophical and cultural meanings.